2022
DOI: 10.3390/ijerph19116395
|View full text |Cite
|
Sign up to set email alerts
|

Precision Behavioral Management (PBM) and Cognitive Control as a Potential Therapeutic and Prophylactic Modality for Reward Deficiency Syndrome (RDS): Is There Enough Evidence?

Abstract: This brief commentary aims to provide an overview of the available and relatively new precision management of reward deficiencies manifested as substance and behavioral disorders. Current and future advances, concepts, and the substantial evidential basis of this potential therapeutic and prophylactic treatment modality are presented. Precision Behavioral Management (PBM), conceptualized initially as Precision Addiction Management (PAM), certainly deserves consideration as an important modality for the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 155 publications
0
4
0
Order By: Relevance
“…Recently, large GWAS studies have revealed a significant dopaminergic gene risk polymorphic allele overlap between depressed and schizophrenic cohorts [157]. A large volume of literature has also identified ADHD, PTSD, and spectrum disorders as having the known neurogenetic and psychological underpinnings of RDS [158][159][160].…”
Section: Induction Of Dopamine Homeostasis Pharmaceuticals and Non-ph...mentioning
confidence: 99%
“…Recently, large GWAS studies have revealed a significant dopaminergic gene risk polymorphic allele overlap between depressed and schizophrenic cohorts [157]. A large volume of literature has also identified ADHD, PTSD, and spectrum disorders as having the known neurogenetic and psychological underpinnings of RDS [158][159][160].…”
Section: Induction Of Dopamine Homeostasis Pharmaceuticals and Non-ph...mentioning
confidence: 99%
“…Theoretical models of addictive disorders handling 'addictions' as a common disorder instead of distinct conditions have already been proposed in the 1980s [14]. More recent research also encourages considering addiction not as a collection of [15] different disorders but as a symbolic umbrella under which all addiction types can be classified. Additionally, Hollander's obsessive-compulsive spectrum disorder (OCSD) model suggests a shared obsessive-compulsive spectrum in the background of psychiatric diseases of different diagnostic categories [15,16].…”
Section: Reward Deficiency Syndrome Index (Rdsi) and Geneticsmentioning
confidence: 99%
“…More recent research also encourages considering addiction not as a collection of [15] different disorders but as a symbolic umbrella under which all addiction types can be classified. Additionally, Hollander's obsessive-compulsive spectrum disorder (OCSD) model suggests a shared obsessive-compulsive spectrum in the background of psychiatric diseases of different diagnostic categories [15,16]. Furthermore, Blum, Cull, Braverman, and Comings in 1996 [17] proposed in the Reward Deficiency Syndrome that the development of impulsive and addictive behaviors shares some common psychological and molecular pathways.…”
Section: Reward Deficiency Syndrome Index (Rdsi) and Geneticsmentioning
confidence: 99%
“…The implication here is that reward is a key element of mental operation that has evolved beyond immediate survival, and it is crucial for most individual and social activities, including emotional attachments, group affiliations, free will, conformity, and obedience to societal norms and edicts (29)(30)(31)(32)(33). Consequently, the lives of individuals with RDS may be intolerable due to their inability to gain full satisfaction from their accomplishments while overcoming the same challenges as others.…”
mentioning
confidence: 99%